2019
DOI: 10.1111/ecog.04412
|View full text |Cite
|
Sign up to set email alerts
|

Alien species richness is currently unbounded in all but the most urbanized bird communities

Abstract: Urban areas suffer high pressure of introductions of alien species compared to other habitats due to intensive human activities. As trading globally continues to rise, more species will likely be introduced into urban areas. To determine whether this increase in introduction pressure will lead to increased alien species richness in urban areas, or whether other processes would act to impose an upper limit on species richness, we examined how the shape of the relationship between alien species richness and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
(124 reference statements)
0
7
0
Order By: Relevance
“…Cities are key points for entry and establishment of invaders. For instance, Cadotte et al (2017) showed that invasive species often occur at higher abundances in urban ecosystems than in the surrounding landscape, while Padayachee et al (2017) found that most urban invasive species are intentionally introduced and then subsequently spread into nearby areas, and Tsang et al (2019) demonstrated that non-native species richness is likely to continue to rise in urban areas globally, especially if introduced species are pre-adapted to urban areas. Urban areas are also hotspots of human movement and the transport of goods, which can promote rapid human-mediated dispersal of non-native species across long distances (Bullock et al 2018).…”
Section: Invasive Species In Urban Areasmentioning
confidence: 99%
See 2 more Smart Citations
“…Cities are key points for entry and establishment of invaders. For instance, Cadotte et al (2017) showed that invasive species often occur at higher abundances in urban ecosystems than in the surrounding landscape, while Padayachee et al (2017) found that most urban invasive species are intentionally introduced and then subsequently spread into nearby areas, and Tsang et al (2019) demonstrated that non-native species richness is likely to continue to rise in urban areas globally, especially if introduced species are pre-adapted to urban areas. Urban areas are also hotspots of human movement and the transport of goods, which can promote rapid human-mediated dispersal of non-native species across long distances (Bullock et al 2018).…”
Section: Invasive Species In Urban Areasmentioning
confidence: 99%
“…and novel natural areas (Møller et al 2015;Cadotte et al 2017;Tsang et al 2019). However, studies are needed to identify underlying traits of these urban species that are advantageous to invasion, and to test whether these traits are selected for during urban evolution.…”
Section: Urban Evolution Promotes Invader Establishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative explanations may include strong biotic resistance, behaviorally induced preferences for urbanized environments and/or time lags in more recent introduction events (e.g. wildlife trade) (Abellán et al 2017, Tsang et al 2019.…”
Section: Posterior Meanmentioning
confidence: 99%
“…Heavily and continuously disturbed industrialized sites (immature novel ecosystems, as defined by Kowarik and von der Lippe 2018) are generally open-canopy locales with intense solar radiation, pollutants, and limited substrate availability. Often, these human-dominated sites are linked to the introduction of nonnative species (Hobbs and Huenneke 1992;Crawley et al 1996;Cadotte and Lovett-Doust 2001;Daehler 2003;Tsang et al 2019;Lucardi et al 2020b). However, both native and nonnative species arriving in industrialized environments may require specific traits conducive to their survival and potentially longer-term establishment that for nonnative species may result in invasive spread (Funk and Vitousek 2007;Cadotte et al 2017;Borden and Flory 2021).…”
Section: Introductionmentioning
confidence: 99%